América Latina en la transición demográfica, 1800-1980. - Pérez Brignoli, Héctor (2010)
This paper was presented in the V Latinamerican Conference of Population; celebrated in Mexico in 1993. Its main idea was the demographical transition in Latin American and the Caribean.